Effects of physical exercise on Autism Spectrum Disorders: A meta-analysis - Sowa, Michelle; Meulenbroek, Ruud (Research in autism spectrum disorders, 2012)
► Physical exercise improves the motor skills of people with Autism Spectrum Disorders. ► Physical exercise improves the social skills of people with Autism Spectrum Disorders. ► Individual physical exercise has positive effects on two problem areas of people with Autism Spectrum Disorders. It is generally agreed that regular physical exercise promotes physical and mental health, but what are the benefits in people with Autism Spectrum Disorders (ASD)? This meta-analysis evaluates 16 behavioural studies reporting on a total of 133 children and adults with various variants of the syndrome who were offered structured physical activities either in an individual or a group context. The effects on social and motor deficiencies, two of the three primary symptom clusters of ASD, were normalized to afford a quantitative evaluation. Results pertaining to communication deficits were insufficient to permit classification. All activity programmes yielded significant progress on the measures assessed, but the individual programmes elicited significantly more improvement than the group interventions in the motor and, more surprisingly, also in the social domain. Although overall sample sizes were small, the combined results do permit the tentative conclusion that in terms of motor performance and social skills children and adults with ASD benefit most from individual exercise interventions. Further research of the impact of individual and group interventions on communication deficits in particular as well as studies gauging the extent to which exercise effects depend on ASD symptom severity are warranted.